Globalisation – Advantages and Disadvantages from the Perspective of the Manufacturer - Adriana Manolic\~a; Teodora Roman (CES Working Papers, 2012)
Years ago, at the beginning of the nuclear age, Einstein asserted that the atomic bomb would completely change the world. Currently, the same can be said about globalization. Globalization, the phenomenon which especially affects economy and life, is now one of the most debated topics in history: lectures, articles, books. Worldwide specialists in economics, politics, and sociology have analyzed in thousands of pages the phenomenon of globalization, its forms, evolution, impact and trends, but the views are so diverse and contradictory that it still is not reached even a universally accepted definition. Perhaps it is the so controversial topic that makes him so attractive. If some persons believe that the phenomenon of globalization ends before reaching its peak, others consider that the current situation is just the beginning of an era in which there are no boundaries.
Keywords: F01; F02; 330; advantages of globalization; disadvantages of globalization Romania